Mediasi Pertanahan sebagai Model Alternatif Penyelesaian Sengketa Hak Ulayat Antara Masyarakat Adat Desa Eti dengan Pemerintah di Kabupaten Seram Bagian Barat Provinsi Maluku - La Ode Angga; Barzah Latupono (Universitas Muhammadiyah Purwokerto, 2020)
This study has long term goals, namely to find a model of dispute resolution of the Indigenous People of the Village of Eti with the Government in the West Seram (SBB). The method of approach used in this research is sociological juridical descriptive qualitative analysis. This study seeks to illustrate what happened in the Eti Indigenous community with the government around the conflict that occurred at the location of this study, namely the West Seram District (SBB). Data collection techniques used in this study are: Interviews, questionnaires and literature studies. Land mediation as an alternative model of dispute resolution between the people of Desa Eti and the SBB government in the following stages; first the team conducted a Dialogue, the Dialok was done well to the people of the Desa Eti with the government involved in a customary land dispute. This is done by the team to find out the desires of the parties in resolving the existing conflict. The second step is to negotiate the two parties involved in land conflicts. This is important in the context of the negotiation process between the two parties to the conflict in the land conflict both from the representatives of the two villages of Eti with the government with the aim of finding mutually beneficial solutions to each other so that both can be open and no one feels disadvantaged, negotiations in a place agreed by both parties. The third step is the team conducting Land Mediation. Mediation was carried out by both parties with the assistance of the team. The method used in this mediation is to resolve this conflict by mediating between the two groups involved in the conflict through the assistance of a neutral third party. The mediator who acts as the mediator has the task of explaining the process and helping both parties to resolve the conflict with the mediation stages prepared by the team. The fourth step is Peace Building (an attempt to restore conditions). We have carried out this effort with the aim of restoring the destructive state caused by violence in the conflict by building bridges of communication between the parties involved in the conflict between the people of Desa Eti and the government. And the fifth rarity is the follow-up supervision stage of the agreement that has been mutually agreed.Keywords: Mediation of Land, Settlement of Disputes, Land Rights